PENERAPAN PROJECT BASED LEARNING (PJBL) BERBANTUAN MICROSOFT EXCEL PADA PEMBELAJARAN STATISTIKA UNTUK MENINGKATKAN PEMAHAMAN MATEMATIS SISWA SMK BRIGJEND KATAMSO 2 MEDAN - Doni Irawan Saragih; Muhammad Rizky Mazaly; Ari Kurniawan (Universitas Samudra, 2022)
The purpose of this study is to determine the improvement of students' mathematical understanding of Statistics learning taught through a Project Based Learning (PjBL) Model assisted by Microsoft Excel at SMK Brigjend Katamso 2 Medan. The samples in this study were students of class XII AK1 as an experimental class and XII AK2 as a control class. The instrument used in this study is a mathematical understanding ability test. The results showed that the average mathematical understanding ability of experimental class students was 90.82 and 77.34 for the control class. The average experimental class pre-test results were 75.00 and 75.62 for the control class. While the average post test results of the experimental class were 90.82 and 77.34 for the control class. Based on the results of the t test conducted, it can be seen that the value of sig.0.000 < 0.05, thus it can be concluded that there was a significant increase in mathematical understanding ability in students of SMK Brigjend Katamso 2 Medan before the implementation of the Project Based Learning (PjBL) Model assisted by Microsoft Excel in Statistics material.